Implementasi Pembelajaran Kontekstual Teaching and Learning dalam Memotivasi Peserta Didik (Penelitian Kualitatif Pada Mata Pelajaran Ekonomi di SMA Negeri 1 Jatiwaras) - Lestari, Sri Dewi; Gumilar, Gugum; Afriza, Edi Fitriana (LPPM Institut Pendidikan Nusantara Global, 2024)
Learning is a process that student must go through every day to achieve the desired goals at school. To achieve this goal, student must be able to follow a series of teaching and learning processes provided by the teacher actively and communicatively. The problem in this research is that students learning motivation is still low. There are still many students who still like to violate academic violations at school. The aim of this research is to analyze the implementation of contextual teaching and learning in motivating students. This research uses a descriptive qualitative method, phenomenological type with triangulation techniques. The informants in this research were the school principal, deputy head of curriculum, economics teacher, and 10 students. The sampling technique used was a purposive sampling technique which was adjusted to the research needs criteria. Data collection methods use interviews, observation and documentation. The research result show thar implementing contextual teaching and learning is able to have a positive impact on increasing students learning motivation, making the learning process more enjoyable and easier to understand.